Airway epithelial integrin β4 suppresses allergic inflammation by decreasing CCL17 production. Issue 13 (10th July 2020) - Yuan, Lin; Zhang, Xun; Yang, Ming; Du, Xizi; Wang, Leyuan; Wu, Shuangyan; Wu, Mengping; Duan, Zhen; Xiao, Gelei; Zou, Yizhou; Xiang, Yang; Qu, Xiangping; et al.
Abstract: Airway epithelial cells (AECs) play a key role in asthma susceptibility and severity. Integrin β4 (ITGB4) is a structural adhesion molecule that is down-regulated in the airway epithelium of asthma patients. Although a few studies hint toward the role of ITGB4 in asthmatic inflammation pathogenesis, their specific resultant effects remain unexplored. In the present study, we determined the role of ITGB4 of AECs in the regulation of Th2 response and identified the underpinning molecular mechanisms. We found that ITGB4 deficiency led to exaggerated lung inflammation and AHR with higher production of CCL17 in house dust mite (HDM)-treated mice. ITGB4 regulated CCL17 production in AECs through EGFR, ERK and NF-κB pathways. EFGR-antagonist treatment or the neutralization of CCL17 both inhibited exaggerated pathological marks in HDM-challenged ITGB4-deficient mice. Together, these results demonstrated the involvement of ITGB4 deficiency in the development of Th2 responses of allergic asthma by down-regulation of EGFR and CCL17 pathway in AECs.